Natural killer T cells in allergic asthma: implications for the development of novel immunotherapeutical strategies - Gutiérrez-Vera, Cristián; García-Betancourt, Richard; Palacios, Pablo A.; Müller, Marioly; Montero, David A.; Verdugo, Carlos; Ortiz, Francisca; Simon, Felipe; Kalergis, Alexis M.; González, Pablo A.; Saavedra-Avila, Noemi A.; Porcelli, Steven A.; et al. (Frontiers in Immunology, 2024)
Allergic asthma has emerged as a prevalent allergic disease worldwide, affecting most prominently both young individuals and lower-income populations in developing and developed countries. To devise effective and curative immunotherapy, it is crucial to comprehend the intricate nature of this condition, characterized by an immune response imbalance that favors a proinflammatory profile orchestrated by diverse subsets of immune cells. Although the involvement of Natural Killer T (NKT) cells in asthma pathology is frequently implied, their specific contributions to disease onset and progression remain incompletely understood. Given their remarkable ability to modulate the immune response through rapid secretion of various cytokines, NKT cells represent a promising target for the development of effective immunotherapy against allergic asthma. This review provides a comprehensive summary of the current understanding of NKT cells in the context of allergic asthma, along with novel therapeutic approaches that leverage the functional response of these cells.